FAKTOR – FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR DI BEI - Devana, Thasya; Sudirgo, Tony (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to find out how the value of profitability, leverage and sales growth on tax avoidance in manufacturing companies listed on Indonesia Stock Exchange during 2018-2020. This research uses a purposive sampling method based on data that matches the criteria are 49 companies. The data processing technique uses multiple regression analysis assisted by the SPSS (Statistical Product and Service Solution) for windows released 16 and Microsoft Excel 2007. The results of this research indicate that there is a significant influence between profitability, leverage and sales growth on tax avoidance. The implication of this research is that there is a tendency for companies to take tax avoidance actions which are caused by high levels of profitability, leverage and sales growth. This is done to maximize the company’s net profit.